Product Defect Analysis of PDH Shirts Using Fault Tree Analysis and Failure Mode and Effect Analysis - Rendi Robintang Siregar; Enny Aryanny (Newinera Publisher, 2025)
CV. Graha Konveksindo Sidoarjo is a manufacturing company that produces garments, with PDH shirts as one of its products. Problems identified at CV. Graha Konveksindo include defects in PDH shirts, totaling 891 pieces, with a defect rate of 12.95 %. This study aims to determine the types and causes of defects and provide suggestions for improvement. The methods used are Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). Based on the study results, four types of defects were found: reverse embroidery with an occurrence probability of 3.53%, untidy stitches with an occurrence probability of 3.34%, off-center emblems with an occurrence probability of 2.36%, and stains with an occurrence probability of 3.13%. Across these defect types, 15 root causes were identified as contributing factors. From the FMEA calculation results, the highest Risk Priority Number (RPN) was found in untidy stitch defects at 252, followed by the reverse embroidery defects emblem defects at 240, off center emblem defects at 210, and stain defects at 160. Some recommended improvement proposals to reduce product defects include providing operator training, conducting briefings before production, and routinely checking sewing and embroidery machines.